A device for detection of bacterial cells - Bilyj, Oleksandr; Yaremyk, Roman; Ferensovich, Yaroslav; Getman, Vasyl'; Grechukh, Taras; Kotsyumbas, Ihor; Kushnir, Ihor (Видавництво Львівської політехніки, 2012)
A device for detection of bacterial cells and results of researches bacterial cells of Escherichia coli and Desulfuromonas of acetoxidans is described.
Keywords: device; bacterial cells; detection